Progressive transition from pre-planned to intraoperative optimizing seed implant: post implementation analysis - Kuo, Hsiang-Chi; Bodner, William; Yaparpalvi, Ravindra; Guha, Chandan; Tolia, Bhupendra M.; Mehta, Keyur J.; Mah, Dennis; Kalnicki, Shalom (Journal of Contemporary Brachytherapy, 2012)
Purpose : To perform a dosimetric comparison between a pre-planned technique and a pre-plan based intraoperative technique in prostate cancer patients treated with I-125 permanent seed implantation. Material and methods : Thirty patients were treated with I-125 permanent seed implantation using TRUS guidance. The first 15 of these patients (Arm A) were treated with a pre-planned technique using ultrasound images acquired prior to seed implantation. To evaluate the reproducibility of the prostate volume, ultrasound images were also acquired during the procedure in the operating room (OR). A surface registration was applied to determine the 6D offset between different image sets in arm A. The remaining 15 patients (Arm B) were planned by putting the pre-plan on the intraoperative ultrasound image and then re-optimizing the seed locations with minimal changes to the pre-plan needle locations. Post implant dosimetric analyses included comparisons of V100(prostate), D90(prostate) and V100(rectum). Results : In Arm A, the 6D offsets between the two image sets were θ x = –1.4 ± 4.3; θ y = –1.7 ± 2.6; θ z = –0.5 ± 2.6; X = 0.5 ± 1.8 mm; Y = –1.3 ± –3.5 mm; Z = –1.6 ± 2.2 mm. These differences alone degraded V100 by 6.4% and D90 by 9.3% in the pre-plan, respectively. Comparing Arm A with Arm B, the pre-plan based intraoperative optimization of seed locations used in the plans for patients in Arm B improved the V100 and D90 in their post-implant studies by 4.0% and 5.7%, respectively. This was achieved without significantly increasing the rectal dose (V100(rectum)). Conclusions : We have progressively moved prostate seed implantation from a pre-planned technique to a pre-plan based intraoperative technique. In addition to reserving the advantage of cost-effective seed ordering and efficient OR implantation, our intraoperative technique demonstrates increased accuracy and precision compared to the pre-planned technique.